Socio-Economic Status of Women Farmers: A Sociological Study of Bhadaure-Tamagi V.D.C., Kaski - Gurung, Santosh Kumar (Himalayan Journal of Sociology and Anthropology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –> The socio-economic status of women farmers is low because of inherent social hierarchy and economic deprivation. The main objective of the study is to find out the socio-economic status of women farmers and to investigate this different research tools is applied mainly interview schedule. The study reveals that although women's agricultural labor force is high but there has not been any significant change in the status of women farmers. Women are still deprived and discriminated in terms economic ground. The Dalits are mainly suffering from this deprivation and discrimination. So, women farmers need a special concern for their livelihood and empowerment. There is an immense need of women empowerment programmes and cash earning packages to break this vicious circle of economic deprivation. DOI: http://dx.doi.org/10.3126/hjsa.v3i0.1500 Himalayan Journal of Sociology and Anthropology Vol.III, Sept. 2008 p.126-138